Mutation Evaluation in P53 exon 5 in Iraqi AML Patients with 4 Growth Levels - Ishtar Imad1, Abdulameer N. Ghaloub1, Mehemt Ozaslan2, Alaa F. Alwan3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The role of TP53 is not limited to repairing damaged DNA and regulating its proliferation, it also activates other repairing genes and prevents mutated DNA from multiplying which prevents malignancy formation that’s why it’s called “ DNA`s gatekeeper”. The aim of current study was to evaluate the role of Exon 5 of P53 gene in the development of AML in Iraqi patients. Method: Sixty newly diagnosed AML patients at Baghdad (haematology national centre) were involved in ccurrent study. Peripheral blood samples were collected in EDTA tubes then they followed a month after receiving 3 and 7 AML treatment regimens to compare mutational status pre and post treatment. The patient divided into 4 age groups based on growth level (0-15 years, 16-40 years, 41-65 years and 66 years and above) in a 15 sample for each. Results: We uncovered transcriptional downregulation of significant p53 acetyltransferases in both CN-AML and APL, joined by expanded Mdmx protein articulation and deficient Chk2 protein enactment. Mutation study on exon 5 of P53 gene showed no differences in gene sequence from the standard sequence of NCBI geneBank sequence. Conclusion: Exon 5 of P53 gene not included in the AML causes since the patients of this study showed no alteration in sequence from the reference sequence